The role of hope according to Ibn Khaldun in securing economic growth : Turkey under the AKP rule from 2002 to 2012 - Yaprak, Aynur (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2015)
This research analyses the writing of Ibn Khaldun in regards to the 'role of hope', and suggest its relevance to Turkish AKP government's reign from 2002 to 2012. It examines policies made by the AKP government in transforming economic and social status of Turkey by creating hope among its people. It provides a brief background to Turkey's economic and social scenarios under various coalition governments until the emergence of the AKP in 2002. It also discusses the process of transformation within the field of human resources, industry and trade, and foreign policies to demonstrate the government's efforts to overcome economic and social problems such as unemployment rate, imbalance in social security, and unequal income distribution. This process of transformation subsequently made a psychological impact and created hope to the Turkish people in participating as members of society and in politics. This research uses the qualitative approach with references from primary and secondary sources on the subject as well as provides statistical data to show the growth of Turkish economy and society. It is hoped that the findings of this research will allow further investigation on the possibilities of incorporating the theories of classical scholars in analysing contemporary socio-economic problems.